Parametric optomechanics - Andrey Matsko; Abdelkrim El Amili; Lute Maleki (APL Photonics)
We investigate two-phonon parametric opto-mechanical generation in a solid state optical cavity pumped with two resonant counter-propagating coherent optical fields. We show that the optical frequencies of the fields must differ by more than the characteristic frequency of the stimulated Brillouin scattering in the material to support the parametric process. The optical harmonics associated with the subsequent optical scattering over the sound waves can be utilized for the excitation of low noise microwave signals.